A survey on antibiotic resistance of Extended-Spectrum beta-lactamase-producing Escherichia coli isolated from urinary tract specimens at Hue University of Medicine and Pharmacy Hospital - Le, Thi Bao Chi; Nguyen, Duc Hoang Sang; Ung, Thi Thuy; Nguyen, Thi Khanh Linh (Tạp chí Y Dược Huế, 2025)
Background: Urinary tract infections caused by Extended-Spectrum β-lactamase (ESBL)-producing Escherichia coli (E. coli) strains are a major concern and a key driver of β-lactam antibiotic group’s resistance. Finding the frequency of ESBL-producing E. coli isolated from urine samples and analyzing their antibiotic resistance profiles were the objectives of this study. Materials and methods: A retrospective, cross-sectional study was conducted on urine samples at Hue University of Medicine and Pharmacy Hospital from January 2023 to April 2024. Bacterial culture, identification, and antibiotic susceptibility testing were performed according to standard microbiology laboratory procedures. Results: 104 ESBL-producing E. coli strains were isolated, accounting for 45.2% of patients with urinary tract infections caused by E. coli. This group was most common in patients over 60 years old, primarily from patients of the Urology outpatient clinic and the Department of General Internal Medicine - Endocrinology - Musculoskeletal and the prevalence was quite similar between males and females (46.9% and 44.6% respectively). The isolates showed high resistance to ampicillin, some cephalosporins, and quinolones, but still remained highly susceptible (>90%) to carbapenems and fosfomycin, and fully susceptible to nitrofurantoin. Conclusion: E. coli producing ESBL are a real burden in the treatment of urinary tract infections. Consequently, investigating the antibiotic resistance profiles of ESBL-producing E. coli in clinical settings is essential for informing physicians’ decisions on appropriate antimicrobial therapy.